The crisis of woodfuel in the Sahel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Le bois-energie au Sahel (Woodfuel in the Sahel) by Hamed Sow ACCT CTA Karthala 1990 in the collection 'Economy and Development' 176 pages ISBN 2 86537 278 2 22-24 boulevard Arago 75013 Paris, FRANCE